Analisis Pengaruh CAR, NPF, FDR, Inflasi, BI Rate terhadap Profitabilitas Bank Umum Syariah di Indonesia: Studi Masa Pandemi Covid-19 - Leni Nur Pratiwi; Selvia Nuria Sari; Hilya Nisa Nur Fadhilah (Jurnal Maps (Manajemen Perbankan Syariah), 2022)
Corona Virus disease 19 is one of the pandemics that has spread to almost all countries in the world, including Indonesia. As a result, it affects not only health sectors, but also the banking system of sharia commercial banks. The purpose of this study was to analyze the influence of CAR, NPF, FDR, Inflation, and BI Rate on the profitability of sharia commercial banks during the Covid-19 pandemic. This research is a quantitative study with secondary data, the number of samples of 10 sharia commercial banks with quarterly financial statements during 2020. This study used the data panel regression analysis method with Random Effect Model approach using Eviews version 9 analysis tool. The results of this study show that CAR has a positive and significant effect on ROA. Furthermore, NPF has a negative and significant effect on ROA. Meanwhile, FDR, Inflation, and Bi Rate have no significant effect on ROA.